2017
DOI: 10.1002/mus.25635
|View full text |Cite
|
Sign up to set email alerts
|

Placebo response in pain, fatigue, and performance: Possible implications for neuromuscular disorders

Abstract: The placebo response in neuromuscular disorders is not well understood. The only available data regarding its underlying mechanisms are related to neuropathic pain. In this review, we describe the factors that contribute to improved outcomes in the placebo arm, with specific attention to pain and fatigue, as well as some of the most important psychobiological mechanisms that may explain such a response. This approach may also improve our insight into the symptomatology and therapeutic responses of other neurom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 105 publications
(129 reference statements)
0
24
0
1
Order By: Relevance
“…The placebo phenomenon is related to patients' perception or direct experience of a treatment, that is seeing, smelling, and hearing verbal information about the treatment and actively integrating this sensory information with memories of previous experiences and current expectations. 16,17 The placebo response is measured as the change in pain observed after administration of the placebo treatment. 18,19 The placebo effect, however, is measured as the difference in pain across an untreated and a placebo-treated group/condition, thereby separating changes in the placebo group from spontaneous fluctuations in pain, regression to the mean, and other confounding factors (Fig.…”
Section: Placebo Analgesia Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The placebo phenomenon is related to patients' perception or direct experience of a treatment, that is seeing, smelling, and hearing verbal information about the treatment and actively integrating this sensory information with memories of previous experiences and current expectations. 16,17 The placebo response is measured as the change in pain observed after administration of the placebo treatment. 18,19 The placebo effect, however, is measured as the difference in pain across an untreated and a placebo-treated group/condition, thereby separating changes in the placebo group from spontaneous fluctuations in pain, regression to the mean, and other confounding factors (Fig.…”
Section: Placebo Analgesia Definitionsmentioning
confidence: 99%
“…Here it is evident that the magnitude of placebo effects is highly variable 22,23 and related to patients' perception of the therapeutic intervention. 16,17 Several attempts have been made to identify stable factors such as demographic variables, 12 personality traits, 82e84 genetic profiles, 46,47, 85 and illness characteristics 86 that may predict a high placebo response, but consistent findings across studies are rare. 82e84 In fact, experimental studies have shown that the same person responds differently to different placebos, 87,88 thereby complicating the notion of a generic placebo responder, that is one that responds consistently to placebo across different situations.…”
Section: Potential Solutionsmentioning
confidence: 99%
“…If this combination of factors leads to a positive expectancy, it will likely result in a beneficial or improved outcome through the placebo effect, whereas negative expectancies could induce harmful outcomes due to the activation of the nocebo effect. Overall, we can state that these phenomena are associated to cognitive–affective factors that can trigger a top-down neural and biochemical modulation of different physiological processes, thus influencing pain (Benedetti, Pollo, & Colloca, 2007; Colloca & Grillon, 2014; Petersen et al, 2014; Price, Craggs, Nicholas Verne, Perlstein, & Robinson, 2007), fatigue (Shaibani, Frisaldi, & Benedetti, 2017), Parkinson’s disease (Frisaldi et al, 2017; Udupa & Fox, 2015), immunity (Tekampe et al, 2017; Wendt, Albring, & Schedlowski, 2014), irritable bowel syndrome (Ballou et al, 2017; Kaptchuk et al, 2010), and the effectiveness of medications (Ader et al, 2010; Bingel et al, 2011; Colloca, Enck, & DeGrazia, 2016), among others. While ethical considerations have always been of concern due to an association of the effectiveness of placebos with deception, newer research has found that placebo effects can occur even when an individual is aware of receiving or having received a placebo intervention (Ballou et al, 2017; Carvalho et al, 2016; Colloca, Pine, Ernst, Miller, & Grillon, 2016; Kaptchuk et al, 2010; Locher et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a future challenge will be the assessment of patients' expectations, the main mediator of the placebo response, and their effects on the therapeutic outcome, in both clinical and experimental settings, as already emphasized for fatigue and performance. 22 We believe that pursuing this line of research would provide important information for both clinical trials and medical practice.…”
Section: Discussionmentioning
confidence: 99%
“…13 The placebo effect in neuromuscular disorders has received little attention; knowledge comes mostly from neuropathic pain 14 and pain in general. [15][16][17][18][19][20][21] However, the placebo response is not the primary objective of these studies, 22 as placebo treatments have been used primarily as control conditions in RCTs of neuromuscular disorders. Despite this limitation, myasthenia gravis (MG) represents an interesting model to investigate placebo responses, as both objective and subjective (e.g., fatigue) symptoms can be assessed.…”
mentioning
confidence: 99%